Determinants of innovation in the health sector - Cifuentes, Jorge; Méndez, Edwin Leonardo; Valenzuela, Silvia Maria (2021)
Innovation in the subsector that relates the activities associated with human health is important because, according to Katz, "this feature has a significant impact on the market behavior and institutional behavior of the agents providing the goods and services necessary to improve or preserve the health of the population” (Katz M., 1995).